Showing particles their place: deterministic colloid immobilization by gold nanomeshes. Issue 30 (15th July 2016) - Stelling, Christian; Mark, Andreas; Papastavrou, Georg; Retsch, Markus
Abstract : Deterministic particle immobilization is a key technique for the fabrication of functional materials via directed self-assembly. Electrostatic interactions allow to selectively adsorb non-close packed latex monolayers onto gold nanomesh arrays with high surface coverage. Abstract : The defined immobilization of colloidal particles on a non-close packed lattice on solid substrates is a challenging task in the field of directed colloidal self-assembly. In this contribution the controlled self-assembly of polystyrene beads into chemically modified nanomeshes with a high particle surface coverage is demonstrated. For this, solely electrostatic interaction forces were exploited by the use of topographically shallow gold nanomeshes. Employing orthogonal functionalization, an electrostatic contrast between the glass surface and the gold nanomesh was introduced on a sub-micron scale. This surface charge contrast promotes a highly site-selective trapping of the negatively charged polystyrene particles from the liquid phase. AFM force spectroscopy with a polystyrene colloidal probe was used to rationalize this electrostatic focusing effect. It provides quantitative access to the occurring interaction forces between the particle and substrate surface and clarifies the role of the pH during the immobilization process. Furthermore, the structure of the non-close packed colloidal monolayers can be finely tuned by varying the ionic strength and geometric parameters between colloidal particles and nanomesh. Therefore one is able to specifically and selectively adsorb one or several particles into one individual nanohole.